2021
DOI: 10.1080/00380768.2021.1991228
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen saturation of forested catchments in central Japan - Progress or recovery?

Abstract: Excess inputs of reactive nitrogen (Nr) from the atmosphere will cause disturbances to forest ecosystems, including soil and stream water acidification, plant nutrient imbalances, alterations of species compositions (such as biodiversity losses), and nitrogen (N) leaching into stream water. Central Japan (or Chubu region) has experienced both domestic and transboundary air pollution since the 1950s. Emissions of nitrogen oxides in China peaked in 2011/2012, although the peak of ammonia emissions has not been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Chiwa et al (2019) suggested that the NO 3 concentration in forest stream water has increased because deer browsing has reduced the understory vegetation. At the Sea of Japan side of the Kajikawa watershed, the stream NO 3 concentration has not decreased despite the lowering trend of nitrogen deposition (Sase et al, 2023). These results suggest that the recovery process from acidic deposition varies among forest ecosystems.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Chiwa et al (2019) suggested that the NO 3 concentration in forest stream water has increased because deer browsing has reduced the understory vegetation. At the Sea of Japan side of the Kajikawa watershed, the stream NO 3 concentration has not decreased despite the lowering trend of nitrogen deposition (Sase et al, 2023). These results suggest that the recovery process from acidic deposition varies among forest ecosystems.…”
Section: Introductionmentioning
confidence: 85%
“…Fresh water chemistry has been generally recovering since the input of acidic deposition was reduced in the United States and European countries (Likens et al, 1996;Stoddard et al, 1999;Oulehle et al, 2017;Lucas et al, 2013) and long-term changes of stream water chemistry in watersheds have been reported in Japan (Chiwa, 2021;Sase et al, 2019;. The sulfate (SO 4 2-) concentration in Japanese watersheds has been decreasing since the 2000s (Sase et al, 2019; but the nitrate (NO 3 -) concentration is more variable, being significantly decreased in some forests but not in others (Chiwa et al, 2019;Sase et al, 2023). Chiwa et al (2019) suggested that the NO 3 concentration in forest stream water has increased because deer browsing has reduced the understory vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive inputs of reactive nitrogen (Nr) from the atmosphere can disrupt forest ecosystems in various ways. These disturbances include acidification of soil and stream water, imbalances in plant nutrients, changes in species compositions leading to biodiversity losses, and leaching of nitrogen (N) into stream water [82]. To understand how climate change will change the structure and function of forest ecosystems, Karnosky et al studied how O 3 affects the flow of carbon through ecosystems from the leaf level to the root and soil microorganisms under current and future atmospheric CO 2 conditions [83].…”
Section: Abstract Analysismentioning
confidence: 99%
“…Past studies reported that the maximum concentration of stream nitrate was 58.4 µM in the KJ forested catchment in Japan, with the maximum value of the M atm / D atm ratio as 9.4 % (Nakagawa et al, 2018;Sase et al, 2022). Whether the index of the M atm / D atm ratio can be applied to forested catchments, where the leaching of stream nitrate is much higher than the KJ forested catchment, remained unclarified.…”
Section: Introductionmentioning
confidence: 99%